Inside your Japanese garden - Yasumoro, Sadao; Cali, Joseph (Tuttle Publishing, 2021)
"Learn how to create a tranquil outdoor space at home with this practical and inspiring guide! With instructive drawings and step-by-step techniques, Inside Your Japanese Garden walks you through designing and creating your very own Japanese garden. From small projects like benches and gates, to larger undertakings like bridges and mud walls, this book provides a wide variety of ways to enhance the space around your home, no matter the size. Instructions on how to work with stone, mud and bamboo as well as a catalogue of the 94 plant varieties used in the gardens shown in the book round out this complete guide. This book also features 20 gardens that author Sadao Yasumoro has designed and built in Japan, and some like those at Visvim shop in Tokyo and at Yushima Tenjin in Tokyo are open to the public. From small tsuboniwa courtyard gardens to a large backyard stroll garden with water features, stairs and walls, these real-life inspirations will help spark your own garden plan. These inspirational garden projects include: Tea Garden for an Urban Farmhouse featuring a clay wall with a split-bamboo frame and a stone base; The Landslide That Became a Garden with a terraced slope, trees, bushes, long grasses and moss; A Buddha's Mountain Retreat of Moss and Stone with vertical-split bamboo and brushwood fencing; Paradise in an Urban Jungle with a pond, Japanese-style bridge, and stone lanterns. Each garden is beautifully photographed by Hironori Tomino and many have diagrams and drawings to show the essential elements used in the planning and construction"--